Dental Caries Experience of Female Inmates - Christine K. Heng, DDS, MPH; Douglas E. Morse, DDS, PhD (Blackwell Synergy, 2002)
The purpose of this study was to determine the extent of dental caries and level of unmet dental need among female offenders in a federal prison in Connecticut.